Detection of Siderophores as a Superior Noninvasive Diagnostic Tool in Unraveling Mixed Fungal Infections - Dobiáš, Radim; Navrátil, Milan; Patil, Rutuja H; Luptáková, Dominika; Stevens, David A; Havlíček, Vladimír (ACS omega, 2025)
Advances in the early diagnosis of systemic mycoses are urgently needed, given the morbidity and mortality of such infections and the correlation between delays in treatment and poor outcomes. We demonstrated the prospective application of liquid chromatography-mass spectrometry in the diagnosis of a mixed fungal infection. In this study, we compared the performance of chest radiography, galactomannan (sGM), and beta-d-glucan (sBDG) serology with a novel diagnostic method based on creatinine-indexed microbial siderophores in urine. A woman with angioblastic T-cell lymphoma presented with neutropenia following allogeneic transplantation. sGM and sBDG remained positive throughout the 28-day intensive care unit stay. A. fumigatus DNA was detected in the induced sputum samples on sampling days 0 and 18. On day 18, a CT scan showed a typical nest sign, and R. microsporus DNA was detected in sputum. The patient was discharged from the hospital on day 28 and expired 7 days later. With our novel strategy based on mass spectrometry, A. fumigatus was consistently detected in the urine from day 0 to the end of the stay by the detection of triacetylfusarinine C (uTafC), an A. fumigatus-specific hydroxamate siderophore. An additional invasive R. microsporus infection was revealed by the detection of a mucoromycete-specific carboxylate siderophore in urine, rhizoferrin (uRhf), from day seven onward. Both creatinine-normalized siderophore indices (uTafC/Cr, uRhf/Cr) were sensitive to antifungal therapy and correlated with fast relapses of the invasive disease in time. This study illustrates how such an early and specific new approach can unravel the complexities of dual fungal infections.